EFFECT OF AT ORVASTATIN ON THE TIME COURSE OF CHANGESIN INFLAMMATORY MARKERS IN SYSTEMIC SCLERODERMA - R T Alekperov; E G Korzeneva; E G Aleksandrova; A A Novikov; L P Anan'eva; E L Nasonov; R T Alekperov; E G Korzeneva; E G Aleksandrova; A A Novikov; L P Ananyeva; E L Nasonov (Научно-практическая ревматология, 2011)
Objective: to study the time course of changes in serological inflammatory markers in patients with systemic scleroderma (SSD) on long-term statin treatment. Subjects and methods. The study covered 40 patients with SSD who were divided into a study group (n = 22) and a control one (n = 18). In the study group, in addition to the therapy performed atorvastatin was given in a dose of 10 mg/day in the first 6 months, 40 mg/day in 12 patients and in the former dose in 10 patients in the following 6 months. Enzyme immunoassay was used to measure the serum level of high-sensitivity C-reactive protein (hs-CRP) and interleukin (IL) 6 in the study group at baseline and after 3, 6, 9, and 12 months of a follow-up and in the control group at baseline and after 12 months. Results. In the study group, the content of hs-CRP was 5.54±4.41 ng/l and increased in 13 (59%) patients. After 3, 6, 9, and 12 months, the level of hs-CRP was 3.93±3.13, 2.95±2.27, 3.15±3.01, and 2.86±2.27 mg/l, respectively, and was significantly lower than the base-line value (p = 0.002). In the same periods, the concentration of hs-CRP decreased by 25, 37, 35, and 35% of the baseline level and remained higher in 10 (45%), 10 (45%), 9 (41%), and 6 (27%) patients, respectively. The level of IL-6 was elevated in 10 of the 14 patients and exceeded in healthy donors. Following 12 months, it decreased from 6.61±6.37 to 1.89±2.71 pg/ml (p = 0.038), and the rate of its increment reduced from 71 to 14% (p = 0.007). In the control group, the levels of hs-CRP and IL-6 as the rate of their increment after 12 months, did not differ from the baseline values. In this group, the changes in the content of hs-CRP and IL-6 in that period were -0.42±2.32 mg/l and 0.14±4.15 ng/ml, respectively, and significantly less marked than those in the study group (p = 0.036 and p = 0.03, respectively). Conclusion. When long used, atorvastatin shows a stable anti-inflammatory effect in most patients with SSD.